APLIKASI SISTEM PENDUKUNG KEPUTUSAN DIAGNOSA PENYAKIT PARU-PARU DENGAN METODE FORWARD CHAINING - Yunus, Mahmud; Setyowibowo, Sigit (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
In Indonesian lung disease have a high death. Tubercolosis (TB) world report (2006) by World Health Organization (WHO), Indonesia still the third biggest after India and China with around 539.000 cases and around 101.000 peoples die for a year. Derived from those fact it need more attention from mass society. My research can be used to decision support system which used to lung disease diagnosed, and know what kind of disease from their symptom. Decision support system use production rule method for representating knowledge about the kind of lung disease and their symptom. This inference engine use tree method and forward chaining. Result derived from this research shown that tree method and forward chaining can be used in finding lung disease from their symptom. Â Key words: tree, forward chaining, lung.